Some Customary Law Nuance on that Hagiography: Attempt of Interpretations - Ščavinskas, Marius (Lietuvos istorijos studijos, 2004)
Early sources about vendetta custom are some papers of the German Order provided in the XIII century. Some of these customs reflect in the Statutes of Lithuania, in some judicial cases of the XVI century, and in modified law records of other Baltic tribes, first of all in the Prussian Pamedė statute-book (XIV). But we can also find vendetta custom in hagiographical sources of late X-early XI centuries, sacred for St. Wojciech and St. Brunon of Querfurt martyrdom in Baltic lands. The motives of murdering the missionaries let us think like that. As St. Vaitiekus came from Polish lands, he was attacked as a Polish agent or ally. Another motive—he was murdered as he was recognized as a person who was dipping people into water (baptizing) or torturing them in other ways. Here we can find elements of vendetta customs. There is no direct data about reasons for murdering St. Brunon in the hagiographic sources provided to him. It is said that Netimer’s brother Zebedene, who probably came when he found out about Netimer’s baptism, told them to kill Brunon. It is worth being said that Netimer, the leader of one of the Baltic tribes, killed his anonymous brother because he didn’t want to be baptized. So the anger of Zebedene was directed against Brunon as the causer of those events. Thus, there also arises a motive of vendetta. According to E. Usačiovaitė, St. Vaitiekus was sacrificed for Baltic gods. But earlier mentioned motives for killing the missionaries don’t allow giving prominence to sacral motives. If St. Vaitiekus was sacrificed to gods, how would Prussians later render his head or body as a ransom to Polish Duke Boleslaw the Brave? In the case of St. Brunon, he could incur the displeasure of pagans when he threw their idols into the fire, but it didn’t happen like that. So, it doesn’t allow denying the vendetta motive for disposing of the first missionaries into Baltic lands.